FLIPPED CLASSROOM SOLUSI MELEJITKAN LOGICAL MATHEMATICAL INTELLIGENCES SISWA DIKALA PANDEMI - Zuha el Widad; Jumari Jumari (Edudeena: Journal of Islamic Religious Education, 2021)
Abstract: The pandemic case causes the shift on the regulation of education in Indonesia therefore, the world needs qualified humans who do not only take part yet create new civilizations. The pandemic era however cannot be mentioned as an obstacle to the learning process. Nowadays in millenial era, the awareness of the importance of knowledge is increased. Flipped Classroom, the media used to transfer the material is applied not only at school but home. In addition, tasks are also worked eithe at home or school. In this case, schools become secondary place where the independence aspect of students become teachers’ main focus thus Flipped Classroom is appropriately applied in this pandemic situation. The main focus of this study are: first, the implementation of flipped classroom combined with map strategy of Hanidifa’s imagination at MA al-Quran La Raiba Hanifida. Second, the application of Flipped Classroom that can improve logical mathematical intelligence skills in fiqh subject. By this research, it is proven that Flipped Classroom can provide the ability to focus, critical attitude and independence skill that can be used as learning model solutions. In this study, the researcher used a qualitative approach. The type of research chosen by the researcher is a case study